A Novel Parabolic Trough Concentrating Solar Heating for Cut Tobacco Drying System - Jiang Tao Liu; Ming Li; Qiong Fen Yu; De Li Ling (International Journal of Photoenergy)
A novel parabolic trough concentrating solar heating for cut tobacco drying system was established. The opening width effect of V type metal cavity absorber was investigated. A cut tobacco drying mathematical model calculated by fourth-order Runge-Kutta numerical solution method was used to simulate the cut tobacco drying process. And finally the orthogonal test method was used to optimize the parameters of cut tobacco drying process. The result shows that the heating rate, acquisition factor, and collector system efficiency increase with increasing the opening width of the absorber. The simulation results are in good agreement with experimental data for cut tobacco drying process. The relative errors between simulated and experimental values are less than 8%, indicating that this mathematical model is accurate for the cut tobacco airflow drying process. The optimum preparation conditions are an inlet airflow velocity of 15 m/s, an initial cut tobacco moisture content of 26%, and an inlet airflow temperature of 200°C. The thermal efficiency of the dryer and the final cut tobacco moisture content are 66.32% and 14.15%, respectively. The result shows that this parabolic trough concentrating solar heating will be one of the heat recourse candidates for cut tobacco drying system.